The Influence of Halal Awareness and Online Customer Review on the Use of Imported Skincare with Purchase Intention as a Moderating Variable - Nabillah Rahmah Widyati; Muhammad Rafi Hartono; Alif Luthfi Muhammad Rasendrio; Herliana Rusmalinda Zainia (Universitas Negeri Surabaya, 2025)
The rapid growth of the skincare industry in Indonesia is influenced by increasing self-care awareness, global beauty trends, and digital media. Moreover, the majority of consumers, who are Muslim, pay attention to halal aspects when making purchasing decisions. This study examines the influence of halal awareness and online customer reviews on the use of imported skincare products, with purchase intention as a mediating factor. Using a quantitative method with 102 respondents in Surabaya, data was collected through an online questionnaire and analyzed with Structural Equation Modeling and Partial Least Squares (SEM-PLS). The results show that halal awareness has a significant effect on the use of imported skincare products, but not on purchase intention. Conversely, online customer reviews have a strong influence on both purchase intention and usage. Purchase intention mediates the relationship between online reviews and usage. These findings highlight the relationship between religious values and digital information in shaping consumer choices, and suggest that skincare product marketers should combine halal transparency with strategic digital engagement to strengthen consumer trust and competitiveness in Indonesia's beauty market.